Novel chiral mesoporous silica nanoparticle and preparation method thereof

Through the design and preparation of new chiral mesoporous silica nanoparticles, the collaborative self-assembly of chiral silicon coupling agent and cetyl trimethyl ammonium bromide is solved by solving the selectivity of achiral drugs in human body. and the problem of poor efficacy has achieved targeted drug delivery and efficient anti-inflammatory effects.

CN119454641APending Publication Date: 2025-02-18SOUTHWEST UNIVERSITY FOR NATIONALITIES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311016235.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to achieve specific selective administration of achiral drugs through triggering biochiral reactions, resulting in poor selectivity and efficacy of drugs in the human body.

Method used

Using novel chiral mesoporous silica nanoparticles, the chiral silicon coupling agent is synthesized by hydrolysis and condensation reaction of L-proline or D-proline and 3-(triethoxysilyl)propylsuccinic anhydride , and self-assembled in conjunction with cetyl trimethylammonium bromide to form mesoporous silica nanoparticles with chiral properties to achieve targeted drug delivery.

Benefits of technology

Through chiral mesoporous silica nanoparticles at the molecular level, the "chirality" of achiral drugs in the biological environment is achieved, the selectivity and efficacy of drugs are improved, and the bioavailability and anti-inflammatory drugs are significantly improved. effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119454641A_ABST
    Figure CN119454641A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of drug delivery, and particularly relates to novel chiral mesoporous silica nanoparticles and a preparation method thereof. The compounds provided by the invention are extracted by the following method: a novel chiral silicon coupling agent TESPSA-L-Pro or TESPSA-D-Pro synthesized by a hydrolytic condensation reaction of L-proline or D-proline (L-Pro or D-Pro) and 3-(triethoxysilyl) propyl succinic anhydride (TESPSA) is used as a structural auxiliary agent (CSDAs), and CMR-L-MSN and CMR-D-MSN with molecular chirality are prepared by synergistic self-assembly. In-vitro drug release research, anti-inflammatory pharmacodynamics and pharmacokinetic results show that the CMR-L-MSN and the CMR-D-MSN have good drug delivery performance for oral insoluble water achiral drugs IMC in vivo or in vitro, which has potential research value for constructing an insoluble water achiral anti-inflammatory drug delivery system, and has broad application prospects. Valuable guidance is provided for development and application of chiral materials in the field of medicine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of drug delivery, and specifically relates to a novel chiral mesoporous silica nanoparticle and a preparation method thereof. Background Art

[0002] Chirality is a geometric property that describes that the mirror image of a structure cannot overlap with the original mirror image. It is widely present in nature and is reflected in the birth and evolution of life. It is well known that most substances that make up our body, such as proteins, nucleic acids, amino acids and polysaccharides, are chiral, which makes us a living being with a chiral environment. With the development of life sciences, on the basis of deeply exploring the chiral nature of the human body, medical researchers have noticed that chiral drugs can express different pharmacological effects when entering the chiral environment of the human body. For example, different racemates correspond to different pharmacological activities, dextropropoxyphene has analgesic effects, and levopropoxyphene has antitussive effects; only one enantiomer has the target pharmacological activity: (S) flurbiprofen can inhibit COX-2 activity and cause anti-inflammatory effects, and (R) flurbiprofen can cause gastrointestinal infections. Therefore, the correct use of chiral drugs can improve efficacy and reduce side effects, which is extremely important in pharmaceutical practice. However, for most achiral drugs, they do not have specific selectivity in the chiral environment of the human body and cannot enjoy the advantages of chiral drugs. In recent years, chiral carriers have attracted much attention due to their unique topological structure, specific biorecognition behavior for the chiral environment of the human body, and in vivo application advantages, as well as their unique advantages in drug (especially achiral drug) delivery. Therefore, designing a new chiral carrier delivery system that can trigger chiral environmental reactions to achieve specific selective administration of achiral drugs can bring drug research to a new level.

[0003] Since the first successful synthesis of highly ordered mesoporous molecular sieve M41s in the early 1990s, mesoporous silica nanoparticles (MSNs) with mesoporous structures (pore size: 2nm to 50nm) have gradually been favored by pharmaceutical researchers due to their excellent specific surface area and pore volume, regular and adjustable pore size, solid and ordered skeleton, excellent thermal stability and physical stability, good biocompatibility and biodegradability, and easy modification and grafting of internal and external surfaces. Therefore, they are widely used in the construction of drug delivery systems. So far, pharmaceutical researchers at home and abroad have developed a variety of drug delivery systems based on MSNs, including rapid release, sustained release, targeted and intelligent response (pH, redox, photothermal, tumor and chiral microenvironmental stimulus response, etc.) triggered release, etc., which have successfully solved the problems of poor bioavailability of poorly soluble drugs and poor clinical application effects.

[0004] With the in-depth study of MSNs, researchers have developed chiral mesoporous silica nanoparticles based on MSNs. For example, researchers used chiral anionic surfactant amino acid derivatives as templates to self-assemble and synthesize supramolecular chiral silica nanoparticles with helical shape, or used cationic surfactant hexadecyltrimethylammonium bromide (CTAB) as template, and APTTES synthesized from APTES and tartaric acid as chiral silicon coupling agent to self-assemble and prepare mesoporous silica nanoparticles with molecular chirality. Compared with MSNs, chiral mesoporous silica nanoparticles not only have the general characteristics of mesoporous silica carriers, but also have chirality at the molecular level, and have the potential to trigger biological chiral reaction systems in the human body, which also makes the drugs loaded into CMSNs may have different drug absorption, distribution, metabolism, pharmacodynamics, transmembrane and protein binding. Therefore, the drug delivery system constructed by chiral mesoporous silica nanoparticles can realize the "handedness" of non-chiral drugs in the biological environment at the molecular level, thereby achieving good therapeutic effects.

[0005] Currently, a variety of formulation strategies have been widely used to construct IMC drug delivery systems, including solid dispersions, microparticles, cyclodextrins, and mesoporous silica nanoparticles, to achieve their solubilization effects and reduce irritation to the gastrointestinal mucosa after administration. However, there are few studies on the use of chiral mesoporous silica nanoparticles at the molecular level with unique advantages to establish drug delivery systems to trigger biological chiral reactions to achieve the best therapeutic effects of IMC. Summary of the invention

[0006] In view of the problems of the prior art, the present invention provides a novel chiral mesoporous silica nanoparticle and a preparation method thereof, aiming to establish a drug delivery system by utilizing chiral mesoporous silica nanoparticles at the molecular level with unique advantages to trigger biological chiral reactions to achieve the optimal therapeutic effect of IMC.

[0007] A novel chiral mesoporous silica nanoparticle is prepared by the following method:

[0008] Step (1): using the hydrolysis condensation reaction of L-proline or D-proline (L-Pro or D-Pro) and 3-(triethoxysilyl)propyl succinic anhydride (TESPSA) to synthesize a novel chiral silicon coupling agent TESPSA-L-Pro or TESPSA-D-Pro, wherein the structural formula of TESPSA-L-Pro is The structural formula of TESPSA-D-Pro is

[0009] Step (2): Dissolve hexadecyltrimethylammonium bromide (CTAB) in a solvent to reach a critical micelle concentration to form micelles, then add a new chiral silicon coupling agent TESPSA-L-Pro or TESPSA-D-Pro. Under alkaline conditions, the negatively charged carboxyl groups and the positively charged hexadecyltrimethylammonium bromide (CTAB) synergistically self-assemble through electrostatic interaction to form a micelle template with siloxane groups. Then, add tetraethyl orthosilicate (TEOS) to react with the siloxane part of the micelle template to form a silicon skeleton. Remove the template to obtain new chiral mesoporous silica nanoparticles CMR-L-MSN and CMR-D-MSN.

[0010] The present invention also provides the use of the novel chiral mesoporous silica nanoparticles in drug delivery:

[0011] 40 mg of oral achiral drug IMC was dissolved in 2 ml of acetone to obtain a high concentration of IMC acetone solution (20 mg / ml), and 80 mg of N-MSN, CMR-L-MSN and CMR-D-MSN carriers were weighed and added to the drug solution to obtain a mixed solution with a drug / carrier ratio of 1:2 (w / w).

[0012] The above mixture was stirred at 300r / min for 24h at room temperature under sealed conditions, then the bottle was opened to wait for the solvent to evaporate completely, the solid mixture was taken out and rinsed with a small amount of pH 7.4 PBS solution 3 times to remove the drug remaining on the surface, and then weighed after drying at 40°C, sealed and protected from light for later use. The obtained drug-loaded carriers were named IMC loaded into N-MSN, IMC loaded into CMR-L-MSN and IMC loaded into CMR-D-MSN.

[0013] Weigh 5 mg of IMC loaded into N-MSN, IMC loaded into CMR-L-MSN and IMC loaded into CMR-D-MSN accurately and place them in a 100 ml brown volumetric flask, dilute to the mark with methanol, and then completely extract the IMC loaded into the carrier pores by ultrasound. After passing through a 0.22 μm filter membrane, dilute the filtrate by an appropriate multiple and measure the absorbance at 318 nm by UV spectrophotometry, and calculate the drug loading amount. Calculate the drug loading rate and drug loading amount according to the following formulas (1) and (2) [2013-Meng Xie].

[0014]

[0015]

[0016] The present invention provides a novel chiral mesoporous silica nanoparticle, which uses chiral mesoporous silica nanoparticles with unique advantages at the molecular level to establish a drug delivery system to trigger biological chiral reactions to achieve the best therapeutic effect of IMC. The drug delivery system constructed by chiral mesoporous silica nanoparticles can realize the "handedness" of non-chiral drugs in the biological environment at the molecular level, thereby achieving good therapeutic effects and having good application prospects.

[0017] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.

[0018] The above contents of the present invention are further described in detail below through specific implementation methods in the form of embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The synthetic route of novel chiral mesoporous silica nanoparticles CMR-L-MSN and CMR-D-MSN is shown;

[0020] Figure 2 The synthetic route (A) and NMR and mass spectrometry results of the new chiral silicon coupling agent TESPSA-L-Pro or TESPSA-D-Pro (B);

[0021] Figure 3 Characterization of N-MSN, CMR-L-MSN and CMR-D-MSN, A is the magnified TEM image, TEM image (100 nm and 200 nm) and particle size distribution of N-MSN, CMR-L-MSN and CMR-D-MSN, respectively, B is the nitrogen adsorption / desorption isotherm of N-MSN, CMR-L-MSN and CMR-D-MSN, C is the pore size distribution curve, and D is the SAXD spectrum;

[0022] Figure 4FTIR, TGA, Zeta potential and ICD analysis, A is the characteristics of FTIR spectra of L-Pro, D-Pro, TESPSA-L-Pro, TESPSA-D-Pro, N-MSN, CMR-L-MSN and CMR-D-MSN, B is the TGA curve of N-MSN, CMR-L-MSN and CMR-D-MSN, C is the potential value of N-MSN, CMR-L-MSN and CMR-D-MSN, D is the ICD spectrum of L-Pro and D-Pro, E is the ICD spectrum of TESPSA-L-Pro and TESPSA-D-Pro, F is the ICD spectrum of CMR-L-MSN and CMR-D-MSN;

[0023] Figure 5 is the interaction between the drug and the carrier and the transition of the drug crystal state of N-MSN, CMR-L-MSN and CMR-D-MSN loaded with IMC, A is the FTIR spectrum, B is the nitrogen adsorption / desorption isotherms of N-MSN, CMR-L-MSN and CMR-D-MSN before and after IMC loading, C is the pore size distribution of N-MSN, CMR-L-MSN and CMR-D-MSN before and after IMC loading, DF is the XRD pattern of IMC, GI is the DSC curve of IMC;

[0024] Figure 6 are the experimental results of in vitro drug release of IMC, IMC-loaded N-MSN, IMC-loaded CMR-L-MSN and IMC-loaded CMR-D-MSN. A, B and C are the in vitro release profiles of IMC, IMC-loaded N-MSN, IMC-loaded CMR-L-MSN and IMC-loaded CMR-D-MSN in pH 6.8 PBS, pH 6.8 PBS-D and pH 6.8 PBS-L, respectively. D, E, F and G are the in vitro release profiles of IMC, IMC-loaded N-MSN, IMC-loaded CMR-L-MSN and IMC-loaded CMR-D-MSN in pH 6.8 PBS, pH 6.8 PBS-D and pH 6.8 PBS-L, respectively. H is the in vitro release profile of IMC-loaded CMR-L-MSN / CMR-D-MSN in pH 6.8 PBS-D and pH 6.8 PBS-L.

[0025] Figure 7The wettability experiment of IMC, A is the initial contact angle of IMC, IMC-loaded N-MSN, IMC-loaded CMR-L-MSN and IMC-loaded CMR-D-MSN in three different pH media, B, C, D are the contact angles of IMC, IMC-loaded N-MSN, IMC-loaded CMR-L-MSN and IMC-loaded CMR-D-MSN measured at different times in pH 6.8PBS, pH 6.8PBS-D and pH 6.8PBS-L respectively;

[0026] Figure 8 The hemolysis rate of silica carrier and the bioadhesion experiment of N-MSN, CMR-L-MSN, CMR-D-MSN and their drug delivery system, A is the hemolysis photos of N-MSN, CMR-L-MSN and CMR-D-MSN, B is the hemolysis rate of N-MSN, CMR-L-MSN and CMR-D-MSN, C is the mucosal bioadhesion properties of N-MSN, CMR-L-MSN and CMR-D-MSN, D is the mucosal bioadhesion properties of IMC, IMC-loaded N-MSN, IMC-loaded CMR-L-MN and IMC-loaded CMR-D-MN;

[0027] Fig. 9 Figure 3 is the in vivo biological effects of IMC-loaded N-MSN, IMC-loaded CMR-L-MSN and IMC-loaded CMR-D-MSN. A is the plasma drug concentration-time curve of IMC, IMC-loaded N-MSN, IMC-loaded CMR-L-MSN and IMC-loaded CMR-D-MSN. B is the therapeutic effect-time curve of normal saline, IMC, IMC-loaded N-MSN, IMC-loaded CMR-L-MSN and IMC-loaded CMR-D-MSN on ankle swelling in rats. A is the curve, C is the levels of TNF-α (pg / ml) and IL-1β (pg / ml) in normal control, saline, IMC, IMC-loaded N-MSNs, IMC-loaded CMR-L-MSNs, and IMC-loaded CMR-D-MSNs, and D is the histopathological changes of the paw skin tissue of rats with swollen ankle joints, and representative pictures are shown (HE staining ×400, ×200, and ×20; blue, green, and black arrows mark lymphocytes, neutrophils, and necrotic lysate tissues, respectively). DETAILED DESCRIPTION

[0028] In the following examples and experimental examples, reagents and raw materials not specifically described are all commercially available products.

[0029] Example 1 Preparation and Formation Mechanism of CMR-L-MSN and CMR-D-MSN

[0030] The current study innovatively uses the new chiral silicon coupling agent TESPSA-L-Pro or TESPSA-D-Pro synthesized by the hydrolysis and condensation reaction of L-proline or D-proline (L-Pro or D-Pro) and 3-(triethoxysilyl)propyl succinic anhydride (TESPSA) as CSDA, and uses CTAB as a cationic surfactant template to trigger the coordinated self-assembly reaction of the system, and then relies on the hydrolysis and deposition reaction of the silicon source to prepare CMR-L-MSN and CMR-D-MSN corresponding to the chiral environment. Scheme 1. shows the synthesis strategy of CMR-L-MSN and CMR-D-MSN. The synthesis mechanism is as follows: CTAB dissolved in a solvent to reach a critical micelle concentration first associates to form micelles. When TESPSA-L-Pro or TESPSA-D-Pro is added, the negatively charged carboxyl groups and the positively charged CTAB synergistically self-assemble under alkaline conditions through electrostatic interaction to form micelle templates with siloxane groups. After TEOS is added, it undergoes a silanization reaction with the siloxane part of the micelle template to form a silicon skeleton, and the template is removed to obtain CMR-L-MSN and CMR-D-MSN. Then, the CTAB needs to be removed by extraction using an ion exchange method, that is, hydrochloric acid is added to the extract (methanol), and the hydrochloric acid will capture the OH- on the non-protonated carboxyl group, so that the electrostatic force that hinders the removal of the surfactant disappears, and the template is dissolved in the extract to obtain CMR-L-MSN and CMR-D-MSN.

[0031] 1. Synthesis of TESPSA-L-Pro and TESPSA-D-Pro

[0032] Under ice bath conditions at 0°C, 884 mg L-Pro or L-Pro was ultrasonically dispersed in 20 ml of anhydrous acetonitrile to form a suspension, and 2.1 ml of triethylamine was added dropwise under stirring. After continuous stirring for 15 min, 2.2 ml of TESPSA was dissolved in 10 ml of dry acetonitrile and added dropwise to the above solution, and the reaction was continued at 0°C with continuous stirring for 2 h. After the reaction, the solvent was removed by rotary evaporation, the crude product was dissolved in 15 ml of ethyl acetate, and the pH was adjusted to about 5 with a pH = 2 HCl solution, and the aqueous solution was repeatedly extracted with an equal volume of ethyl acetate for 6 times. After the organic phase was dried over Na2SO4, it was dissolved in 15 ml of anhydrous ethanol and 15 ml of dichloromethane and evaporated to dryness repeatedly to obtain a white hygroscopic foam, namely TESPSA-L-Pro and TESPSA-D-Pro.

[0033] The molar ratio of L-proline or D-proline (L-Pro or D-Pro) to 3-(triethoxysilyl)propyl succinic anhydride (TESPSA) is 1:2 to 2:1, preferably 1:1.

[0034] 2. Synthesis of N-MSN, CMR-L-MSN and CMR-D-MSN

[0035] Place 1.2g CTAB in a beaker, add 150ml deionized water and 45ml anhydrous ethanol, and stir at room temperature until dissolved; add 1.2ml ammonia water and 0.45g TESPSA-L-Pro or TESPSA-D-Pro in turn under stirring, stir evenly, then slowly add 3.75ml TEOS, continue stirring for 4h, and let stand for 24h; centrifuge at 10000-12000rpm for 5-10min to obtain a white precipitate, wash it with deionized water and ethanol three times each, and dry it at 60℃; heat and reflux it with 0.02mol / L HCl methanol solution for 12h, centrifuge it at 10000rpm for 5min, and wash it with deionized water and ethanol three times each to obtain CMR-L-MSN and CMR-D-MSN. The synthesis method of N-MSN is the same except that TESPSA-COOH is not added.

[0036] The molar ratio of hexadecyltrimethylammonium bromide (CTAB) to the novel chiral silicon coupling agent TESPSA-L-Pro or TESPSA-D-Pro is 2:1 to 4:1, preferably 3:1.

[0037] In addition, the chemical structure and molecular weight of TESPSA-L-Pro or TESPSA-D-Pro were further confirmed by 1HNMR and LC / MS. The synthesis route is shown in Fig. 1A, and the results of NMR and mass spectrometry (Fig. 1B) show that TESPSA-L-Pro: 1H NMR (400MHz, MeOD): δ4.91(s,1H),4.47–4.35(m,1H),3.95–3.74(m,4H),3.64 –3.56(m,2H),3.34–3.27(m,1H),3.22–3.18(m,2H),2.73–2.58(m,1H),2.55– 2.37(m,1H),2.30–2.18(m,1H),2.14–1.86(m,3H),1.62–1.41(m,2H),1.35–1 .28(m,2H),1.28–1.14(m,9H),0.82–0.56(m,2H); LCMS(ESI)m / z:417.9[MH]-. TESPSA-D-Pro: 1H NMR(400MHz,MeOD)δ4.95(s,1H),4.42–4.35(m,1H),3.93–3.77(m,4H),3.65– 3.55(m,2H),3.33–3.28(m,1H),3.24–3.15(m,2H),2.72–2.53(m,1H),2.50–2 .35(m,1H),2.32–2.15(m,1H),2.10–1.94(m,3H),1.59–1.45(m,2H),1.35–1. 25(m,2H),1.25–1.13(m,9H),0.80–0.56(m,2H); LC / MS(ESI)m / z:417.9[MH]-. The above results showed that TESPSA-L-Pro and TESPSA-D-Pro were successfully synthesized.

[0038] Examples 2-6 all used TESPSA-L-Pro and TESPSA-D-Pro prepared in Example 1 to conduct experiments.

[0039] Example 2 Characterization of N-MSN, CMR-L-MSN and CMR-D-MSN

[0040] 1. Transmission Electron Microscopy (TEM)

[0041] Appropriate amounts of sample powders N-MSN, CMR-L-MSN and CMR-D-MSN were ultrasonically dispersed in anhydrous ethanol, and carefully dropped onto a micro-grid copper grid coated with a carbon film, and dried at an appropriate temperature. The samples were placed on the operating table, evacuated, and TEM images were observed and recorded at an accelerating voltage of 200 kV.

[0042] 2. Infrared analysis (IR)

[0043] Take appropriate amount of dry sample powder L-Pro, D-Pro, TESPSA-L-Pro, TESPSA-D-Pro, N-MSN, CMR-L-MSN and CMR-D-MSN and grind and mix with dry KBr under infrared lamp. After pressing into transparent thin sheets by tablet press at 10-20F / cm2, scan in the scanning range of 400-4000cm-1 and assign characteristic peaks.

[0044] 3. Circular dichroism analysis (ICD)

[0045] Take appropriate amount of dry sample powder L-Pro, D-Pro, TESPSA-L-Pro, TESPSA-D-Pro, CMR-L-MSN and CMR-D-MSN and grind them together with dry KBr, press them into transparent sheets under a certain pressure, and then install them on a circular dichroism spectrometer for testing.

[0046] 4. Pore size and specific surface area determination (BET)

[0047] Weigh about 0.1g and put it into a sample tube for pretreatment at 90℃ for 30min. After the pretreatment, the accurate mass of the sample is obtained by weight loss method, and then the specific surface area and pore size test are performed. The specific surface area of ​​the sample is obtained according to the BET data in the relative pressure range of 0.05 to 0.2 using the Brunauer-Emmett-Teller method. The total pore volume of the sample is obtained by using the N2 adsorption amount at a relative pressure (P / P0) of 0.99. The pore size distribution is determined using the Barrett-Joyner-Halenda (BJH) method using the adsorption branch of the corresponding isotherm.

[0048] 5. Zeta potential and particle size analysis

[0049] Take appropriate amount of dry sample powder N-MSN, CMR-L-MSN and CMR-D-MSN, ultrasonically disperse them in anhydrous ethanol, and test them on a machine to determine their particle size and Zeta potential.

[0050] 6.TGA analysis

[0051] Thermogravimetric (TGA) measurements were performed on N-MSN, CMR-L-MSN and CMR-D-MSN samples using a microcomputer differential thermal analyzer (HCT-1, Beijing, China) with air as carrier gas as blank control to determine the modified groups. 3-5 mg samples were treated to 800 °C.

[0052] 7. Small angle X-ray diffraction (SAXD)

[0053] SAXD analysis of N-MSN, CMR-L-MSN and CMR-D-MSN samples was performed using a SAXD system (D8 ADVANCE, Brook AXS, France) at 2θ angles of 0.1° to 6°. The experimental conditions were Cu-Ka radiation with Ni filter, tube voltage of 40 kV and tube voltage of 50 mA.

[0054] Conclusion: TEM and particle size analysis were used to characterize the morphology and particle size of N-MSN, CMR-L-MSN and CMR-D-MSN. The experimental results are shown in Fig. 2A. N-MSN, CMR-L-MSN and CMR-D-MSN are all spherical monodisperse nanoparticles with rough surfaces and irregular honeycomb pores, with an average diameter ranging from 100nm to 300nm. The particle sizes of CMR-L-MSN (245.7nm) and CMR-D-MSN (251.2nm) are larger than those of N-MSN (135.6nm) and show a more clearly visible pore structure. This suggests that in the presence of the carboxyl group of TESPSA-L-Pro and TESPSA-D-Pro, the trimethylamine group of CTAB produces a synergistic self-assembly effect that accelerates the process of silicon mineralization, thereby forming CMR-L-MSN and CMR-D-MSN with larger particle sizes and more clearly visible pore structures. In addition, CMR-L-MSN and CMR-D-MSN have a "thick core-thin shell" structure with a rougher surface. The reason is that compared with TEOS, TESPSA-L-Pro and TESPSA-D-Pro have a lower concentration of silanol groups, which are dispersed on the outer shell of silica microspheres, resulting in a looser silicon density of CMR-L-MSN and CMR-D-MSN [2020-Lulu Wu], resulting in a loose and rough appearance with a tight inner core and a loose outer shell. In order to further study their specific surface area and pore size, this study conducted N2 adsorption / desorption experiments. The data showed that the DP of N-MSN, CMR-L-MSN and CMR-D-MSN were 2.2nm, 2.4nm and 2.7nm, respectively, all falling within the range of 2nm to 50nm, and all showed isotherms with hysteresis loops (type IV), so they are all mesoporous silica nanomaterials (Fig. 2B and 2C). Interestingly, due to the synergistic self-assembly effect of the carboxyl groups of TESPSA-L-Pro and TESPSA-D-Pro, the SBET (1141, 1075m2 / g) and Vt (0.986, 0.988cm3 / g) of CMR-L-MSN and CMR-D-MSN have no significant difference, but are significantly higher than the SBET (724m2 / g) and Vt (0.835cm3 / g) of N-MSN (Table 1). In addition, it can be seen from Fig. 2D that there is no obvious diffraction peak on the SAXD curve of N-MSN, indicating that monodisperse silica has a lower ordered mesostructure. However, CMR-L-MSN has obvious diffraction peaks at 1.6° and 3.0°, and CMR-D-MSN has obvious diffraction peaks at 1.5° and 2.9°, indicating that the order of its mesostructure is higher than that of monodisperse silica, and it can be seen. This may be due to the cooperative self-assembly reaction of carboxyl groups in hyd-TESPSA leading to the ordered stacking of silicon sources, which also affects the ordered stacking of mesoporous channels.Compared with CMR-L-MSN, the characteristic diffraction peaks of CMR-D-MSN all shift to smaller angles, indicating that it has a larger lattice constant and lattice spacing, which is consistent with the TEM observation results.

[0055] In order to further prove the modification of CMR-L-MSN and CMR-D-MSN by TESPSA-L-Pro and TESPSA-D-Pro, FTIR, TGA, Zeta potential and ICD analysis were performed in this study. Fig.3A shows the infrared spectrum data of the relevant samples. Infrared spectra cannot explain the chirality difference, so the spectra of TESPSA-L-Pro and TESPSA-D-Pro are almost the same. Their spectra both show the C=O stretching vibration peak of amide at 1609.6cm-1, proving that L-Pro and D-Pro are successfully hydrolyzed and condensed with TESPSA. At the same time, TESPSA-L-Pro and TESPSA-D-Pro also show the C=O stretching vibration peak of carboxyl at 1731.9cm-1, and the bending vibration peak of -OH of carboxyl at 908.2cm-1, indicating that they have achieved carboxyl modification. In addition, they all show CH stretching vibration peaks at 2987.9 and 2784.1cm-1. The above characteristic peaks preliminarily confirmed the structure of TESPSA-L-Pro and TESPSA-D-Pro. The spectra of N-MSN, CMR-L-MSN and CMR-D-MSN all showed asymmetric stretching vibration absorption peaks of Si-O-Si at 1083.9, 1071.9 and 1077.5 cm-1, and a bending vibration absorption peak of Si-O-Si at 458.3 cm-1; asymmetric stretching vibration peaks of hydroxyl in Si-OH were shown at 3455.3, 3444.0 and 3437.7 cm-1, respectively. The infrared spectrum results preliminarily judged that the mesoporous silica nanoparticles were successfully synthesized. In addition, the spectra of TESPSA-L-Pro and TESPSA-D-Pro Figure 1The results showed that CMR-L-MSN and CMR-D-MSN showed a stretching vibration peak of C=O in the carboxyl group at 1726.3 cm-1, and a bending vibration peak of -OH in the carboxyl group at 949.6 cm-1. The infrared spectrum results preliminarily judged that CMR-L-MSN and CMR-D-MSN had been successfully modified by TESPSA-L-Pro and TESPSA-D-Pro, respectively. The TGA curves of N-MSN, CMR-L-MSN and CMR-D-MSN showed (Fig.3B) that the total weight loss rates were 6.9%, 20.6% and 20.8%, respectively. Before 200℃, the weight loss of N-MSN (3.5%), CMR-L-MSN (5.7%) and CMR-D-MSN (7.9%) was due to the evaporation of water in the sample and the partial water loss of Si-OH units condensed in the pore wall. Their further weight loss in the range of 200-800 ° C is attributed to the removal of organic groups in the sample. The weight loss of Si-OH in N-MSN is 3.5%, and the further weight loss in CMR-L-MSN (14.9%) and CMR-D-MSN (12.9) is the modified organic group. At the same time, the zeta potential of CMR-L-MSN and CMR-D-MSN modified with carboxyl groups in TESPSA-L-Pro and TESPSA-D-Pro decreased from -16.5 mV to -28.5 and -29.2 mV (Fig. 3C). All of the above proves that CMR-L-MSN and CMR-D-MSN were successfully modified by TESPSA-L-Pro and TESPSA-D-Pro. ICD analysis was used to further study the chirality of CMR-L-MSN and CMR-D-MSN (Fig. 3D-F). L-Pro and D-Pro showed positive and negative absorption peaks in the electronic absorption range of 210-220nm. The new chiral silicon coupling agents TESPSA-L-Pro or TESPSA-D-Pro synthesized after hydrolysis and condensation reaction with TESPSA showed chirality reversal. CMR-L-MSN and CMR-D-MSN synthesized by CSDA collaborative self-assembly with TESPSA-L-Pro or TESPSA-D-Pro were successfully endowed with consistent chirality.

[0056] Example 3 Drug loading and crystalline state

[0057] 1. Drug loading process

[0058] 40 mg of IMC was dissolved in 2 ml of acetone to obtain a high concentration of IMC in acetone solution (20 mg / ml), and 80 mg of N-MSN, CMR-L-MSN and CMR-D-MSN carriers were weighed and added to the drug solution to obtain a mixed solution with a drug / carrier ratio of 1:2 (w / w). The above mixture was stirred at a speed of 300 r / min at room temperature under sealed conditions for 24 hours, and then the bottle mouth was opened to wait for the solvent to evaporate completely, and the solid mixture was taken out and rinsed with a small amount of pH 7.4 PBS solution 3 times to remove the drug remaining on the surface, and then weighed after drying at 40°C, and sealed and protected from light for later use. The obtained drug-loaded carriers were named IMC loaded into N-MSN, IMC loaded into CMR-L-MSN and IMC loaded into CMR-D-MSN. 5 mg of IMC loaded into N-MSN, IMC loaded into CMR-L-MSN and IMC loaded into CMR-D-MSN were accurately weighed and placed in a 100 ml brown volumetric flask, and the volume was fixed to the mark with methanol. Then, the IMC loaded into the carrier pores was completely extracted by ultrasound. After passing through a 0.22 μm filter membrane, the filtrate was diluted by an appropriate multiple and the absorbance was measured at 318 nm by ultraviolet spectrophotometry, and the drug loading amount was calculated. The drug loading rate and drug loading amount were calculated according to the following formulas (1) and (2).

[0059]

[0060]

[0061] 2. Characterization before and after drug loading

[0062] FTIR analysis

[0063] Fourier transform infrared spectroscopy was used to analyze the possible interactions between drugs and carriers during drug loading. The infrared spectra of the samples (N-MSN, CMR-L-MSN, CMR-D-MSN, IMC, IMC loaded into N-MSN, IMC loaded into CMR-L-MSN and IMC loaded into CMR-L-MSN) were measured in the spectral region of 400-4000 cm-1.

[0064] 2.2. N2 adsorption and desorption analysis

[0065] V-Sorb 2800P (app-one, China) was used to conduct nitrogen adsorption and desorption experiments on samples (N-MSN, CMR-L-MSN, CMR-D-MSN, IMC loaded into N-MSN, IMC loaded into CMR-L-MSN and IMC loaded into CMR-L-MSN) to study the changes in their specific surface area, pore volume and pore size. All samples were pretreated at 90 °C for 6 hours before analysis to remove the moisture adsorbed on the surface.

[0066] 2.3. Zeta potential and particle size analysis

[0067] Zeta potential and particle size were measured by Zetasizer Nano ZS (Malvern Instruments, Malvern, UK). Before testing, all samples (N-MSN, CMR-L-MSN, CMR-D-MSN, IMC loaded into N-MSN, IMC loaded into CMR-L-MSN and IMC loaded into CMR-L-MSN) were dispersed in anhydrous ethanol by ultrasonication.

[0068] 3. Transition of drug crystal state

[0069] 3.1. X-ray diffraction (XRD)

[0070] A series of samples including N-MSN, CMR-L-MSN, CMR-D-MSN, IMC loaded into N-MSN, IMC loaded into CMR-L-MSN, IMC loaded into CMR-L-MSN and physical mixture of IMC with N-MSN, CMR-L-MSN and CMR-D-MSN were ground and plated, and the changes of drug crystal form before and after drug loading were studied using EMPYREAN XRD (PANalytical BV, Netherlands). The measurement conditions were: Cu target, Ka radiation source, tube voltage 40 kV, tube current 30 mA, scanning angle 4° / min, scanning angle 5 to 45°, and step size 0.04°.

[0071] 3.2. Differential Scanning Calorimetry (DSC)

[0072] A microcomputer differential thermal analyzer (HCT-1, Beijing, China) was used to perform DSC measurements on a series of samples including N-MSN, CMR-L-MSN, CMR-D-MSN, IMC loaded into N-MSN, IMC loaded into CMR-L-MSN, IMC loaded into CMR-L-MSN, and physical mixtures of IMC with N-MSN, CMR-L-MSN, and CMR-D-MSN to analyze their crystal state. The samples were placed in a small dry pot and the temperature was raised from 30°C to 300°C at a heating rate of 10°C / min.

[0073] Conclusion: In this study, the achiral oral anti-inflammatory drug IMC was selected as a model drug and loaded into N-MSN, CMR-L-MSN and CMR-D-MSN by solvent evaporation method. The drug loading rate and drug loading of IMC loaded into CMR-L-MSN (drug loading rate: 97.3±1.0%, drug loading amount: 32.4±0.4%) and CMR-D-MSN (drug loading rate: 97.1±1.1%, drug loading amount: 32.3±0.4%) were higher than those of IMC loaded into N-MSN (drug loading rate: 93.8±1.0%; drug loading amount: 31.3±0.3%), which is consistent with the larger surface area, pore volume and pore size of CMR-L-MSN and CMR-D-MSN. Infrared spectroscopy analysis confirmed that IMC can be effectively loaded into N-MSN, CMR-L-MSN and CMR-D-MSN (Fig. 4A). In the infrared spectrum of IMC, the carbonyl stretching vibration peaks of carboxylic acid and amide can be observed at 1699.1cm-1 and 1593.6cm-1, respectively, and the characteristic peaks such as CN stretching vibration peak and aromatic ether stretching vibration peak are shown at 1312.7cm-1 and 1221.0cm-1, respectively. When IMC is loaded into N-MSN, CMR-L-MSN and CMR-D-MSN, the infrared spectrum shows that the carbonyl stretching vibration peak of carboxylic acid is red-shifted (1687.1, 1683.0, 1688.8cm-1, respectively), and the stretching vibration peak of aromatic ether almost disappears. These results all confirm the result of hydrogen bonding between IMC and silanol groups in the pores of N-MSN or carboxyl groups in the pores of CMR-L-MSN and CMR-D-MSN, which further proves that IMC is successfully loaded into the pores. After IMC is loaded into N-MSN, CMR-L-MSN and CMR-D-MSN, its specific surface area, pore volume and pore size will change, so this study uses N2 adsorption / desorption experiments for further analysis and characterization. The results show (Fig.4Band 4C and Table 1) that when IMC is loaded into N-MSN, CMR-L-MSN and CMR-D-MSN, their specific surface area, pore volume and pore size are significantly reduced. This further proves that IMC can be effectively loaded into their mesoporous channels.

[0074] The crystal state of IMC before and after drug loading was further studied by XRD and DSC analysis (Fig.4D-I). XRD results show (Fig.4D-F) that no crystal diffraction peaks were observed in the spectra of N-MSN, CMR-L-MSN and CMR-D-MSN, and they all showed typical broad peaks, indicating that both carriers were in an amorphous state. The spectrum of IMC clearly showed a large number of sharp diffraction peaks, indicating that it has a highly crystalline structure. The physical mixtures of IMC and their carriers showed several strong drug diffraction peaks. Compared with the physical mixture, there were almost no drug diffraction peaks after IMC was loaded into N-MSN, CMR-L-MSN and CMR-D-MSN, indicating that some drugs had undergone a crystal transformation and existed in an amorphous state. This may be because the limited nanoscale pore size of N-MSN, CMR-L-MSN and CMR-D-MSN nanocarriers has a certain restriction on the crystallization of drugs and does not have the conditions for crystallization, resulting in the existence of drugs in an amorphous state. At the same time, the DSC results show (Fig. 4G-I) that IMC has obvious endothermic peaks at around 160°C, indicating that it is in a crystalline state. No endothermic peaks were observed in N-MSN, CMR-L-MSN and CMR-D-MSN, indicating that the carrier is in an amorphous state. NMS, IMC and physical mixtures showed obvious endothermic peaks at around 150 and 160°C, further confirming the crystalline state of NMS and IMC. The endothermic peak of the drug in the drug-loaded carrier at 160°C is extremely weak, much smaller than that of the physical mixture, indicating that the drug in the drug-loaded carrier has undergone a crystal change, and the drug is almost entirely in an amorphous state. In short, the results of XRD and DSC are highly consistent, which together illustrate that the drug undergoes a crystal transformation after being loaded into the carrier.

[0075] Example 4 Drug Release and Wettability

[0076] The in vitro dissolution of IMC was determined according to the USPII paddle method using a ZRD 6-B dissolution apparatus (Shanghai Huanghai Pharmaceutical Testing Instrument Factory, China) at (37±0.1)°C with a stirring speed of 50 rpm. IMC (7 mg), IMC loaded into N-MSNs, IMC loaded into CMR-L-MSNs, and IMC loaded into CMR-L-MSNs (all containing 7 mg IMC) were accurately weighed and placed in 250 ml of dissolution medium (three types: pH 6.8 PBS, pH 6.8 PBS-L, and pH 6.8 PBS-D). 5 ml of the sample was taken out at the pre-set time points (2 min, 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 45 min, 1 h, 1.5 h, and 2 h), and 5 ml of dissolution medium was added after each sampling to maintain a constant volume. After the sample was filtered through a 0.22 μm microporous filter membrane, the absorbance was measured at a wavelength of 318 nm using a UV-1750 ultraviolet-visible spectrophotometer. All in vitro dissolution experiments were performed in parallel 3 times, and the cumulative release amount was calculated and the dissolution curve was drawn.

[0077] Conclusion: The dissolution experiments in this study were all carried out under sink conditions. As shown in Fig.5A, under the dissolution conditions of pH 6.8 PBS, the release of IMC in CMR-L-MSN (91.5±0.7%) and CMR-D-MSN (93.7±2.2%) was significantly higher than that in N-MSN (85.6±2.5%) and IMC (79.1±3.3%) (p<0.05, p<0.01). This is attributed to their higher specific surface area, larger pore volume and pore size after modification, which leads to higher drug loading and more amorphous IMC in the carrier. The release amount and release rate of IMC by CMR-D-MSN were slightly larger than those by CMR-L-MSN, which suggests that there may be some differences in the release of IMC by carriers with different chiral structures. It is well known that the amino acids that make up proteins and enzymes are L-type. Enantiomers of different configurations are absorbed in different ways in the body and exhibit different physiological and pharmacological effects. Therefore, CMR-L-MSNs and CMR-D-MSNs with molecular-level chiral functions can trigger the chirality of the biological environment and have great value in controlling the bioavailability of drugs to achieve specific purposes. Therefore, in order to further study the release of IMC by CMR-D-MSN and CMR-L-MSN in different chiral environments, this study selected L-alanine and D-alanine (both at a concentration of 0.5 mg / ml) chiral small molecules to simulate the chiral environment of the human body for drug release research. In different chiral environments, the release of IMC in CMR-D-MSN and CMR-L-MSN showed differences in chiral recognition, which can significantly improve the release capacity of IMC. In pH 6.8 PBS-D, the release amount of IMC in CMR-L-MSN (94.0±3.2%) and CMR-D-MSN (95.3±3.1%) was similar, and the release rate in CMR-L-MSN was slightly higher than that in IMC (72.6±2.4%), which was significantly increased (p<0.01). The release of IMC in CMR-D-MSN was significantly increased compared with that in N-MSN (87.0±4.2%) (p<0.05) (Fig.5B). In 6.8PBS-L, the release of IMC in CMR-D-MSN (97.6±2.3%) was significantly higher than that in CMR-L-MSN (92.7±0.9%) (p<0.05), and their release was significantly higher than that of IMC (72.8±4.4%) (p<0.01). Compared with N-MSN (85.5±5.9%), the release of IMC in CMR-D-MSN was also significantly increased (p<0.05) (Fig.5C). In addition, as can be seen from Fig.5D and 5E, the release of IMC was significantly inhibited in a chiral environment, and IMC loaded into N-MSN did not show obvious chiral recognition release advantages.Interestingly, in different chiral media pH 6.8PBS-L and pH 6.8PBS-D, both CMR-L-MSN and CMR-D-MSN can significantly increase the release of IMC. Among them, IMC loaded into CMR-L-MSN has the largest release in pH 6.8PBS-D (Fig.5F), IMC loaded into CMR-D-MSN has the largest release in pH 6.8PBS-L (Fig.5G), and IMC loaded into CMR-D-MSN in pH 6.8PBS-L has a significantly higher release than IMC loaded into CMR-L-MSN in pH 6.8PBS-D (p<0.05) (Fig.5H). In summary, both CMR-D-MSN and CMR-L-MSN can significantly increase the release of IMC and have specific recognition functions in chiral microenvironments, among which CMR-D-MSN has a greater advantage in drug release. The reason is closely related to the influence of their mesoscopic properties such as specific surface area, pore volume and pore size and the chiral structure at the molecular level on drug release. In the future, it is necessary to further verify the specific drug release of CMR-D-MSN and CMR-L-MSN in response to the chiral microenvironment at the molecular level.

[0078] In order to further verify the effect of different dissolution media on the release of IMC in CMR-D-MSN and CMR-L-MSN, wettability experiments were conducted in this study. The initial wetting angle measurement results of IMC, IMC loaded into N-MSN, IMC loaded into CMR-D-MSN and IMC loaded into CMR-L-MSN are shown in Fig.6A. In the dissolution medium, IMC loaded into CMR-D-MSN and IMC loaded into CMR-L-MSN had smaller initial contact angles than IMC and IMC loaded into N-MSN, suggesting that they all showed good wettability, among which IMC loaded into CMR-D-MSN (44.8±0.2°) showed the best wetting effect in pH 6.8 PBS-L. As the contact time between the dissolution medium and the drug delivery system increased, their contact angles showed a gradual decrease. In the medium of pH 6.8 PBS, after 3 min, the contact angle of IMC loaded into CMR-L-MSN (38.6±0.1°) was significantly reduced compared with IMC (41.7±0.6°) (p<0.05). The contact angle of IMC loaded into CMR-D-MSN (35.4±0.3°) was greatly reduced compared with IMC, IMC loaded into N-MSN (39.1±0.4°) and IMC loaded into CMR-L-MSN (p<0.01) (Fig.6B). In the medium of pH 6.8PBS-D and pH 6.8PBS-L, after 3 min, the contact angles of IMC loaded into CMR-L-MSNs (pH 6.8PBS-D: 35.1±0.3°; pH 6.8PBS-L: 37.2±0.1°) and IMC loaded into CMR-D-MSNs (pH 6.8PBS-D: 34.1±0.2°; pH 6.8PBS-L: 33.9±0.3°) were significantly reduced compared with IMC and IMC loaded into MSNs (p<0.01). Among them, the contact angle of IMC loaded into CMR-D-MSNs was significantly reduced compared with that of IMC loaded into CMR-L-MSNs (p<0.01) (Fig.6C and6D), which still showed that IMC loaded into CMR-D-MSNs had a good wetting effect. In summary, IMC loaded into CMR-D-MSN and IMC loaded into CMR-L-MSN have excellent wetting effects, which is attributed to the large number of carboxyl groups on their surfaces, which are more hydrophilic than the silanol groups on MSN, thus enabling them to adsorb water molecules from a humid environment and improve wettability. In addition, their wettability results further verify their drug release of IMC in different dissolution media.

[0079] Example 5 Blood compatibility and bioadhesion

[0080] Hemolysis test: In order to evaluate the blood compatibility of CMR-L-MSN and CMR-D-MSN, a hemolysis test was performed by comparing with N-MSN. First, blood was collected from the orbital vein of SD rats (heparin tube), centrifuged (2000rpm centrifugation for 10min), and the red blood cells were repeatedly washed 3 times with sterile saline until the supernatant was clear, and diluted with sterile saline to form a red blood cell suspension with a volume fraction of 2%. Then, a certain concentration of N-MSN, CMR-L-MSN and CMR-D-MSN suspension (200μg / ml, 400μg / ml, 800μg / ml, 1600μg / ml) prepared with saline was mixed with an equal volume of red blood cell suspension to prepare suspensions with concentrations of 100μg / ml, 200μg / ml, 400μg / ml, and 800μg / ml as sample groups. In addition, a 2% red blood cell suspension was mixed with an equal volume of sterile saline and an equal volume of distilled water as a negative control group and a positive control group, respectively. Finally, the prepared suspension was gently shaken at 37°C for 4 hours, centrifuged at 1000 rpm for 10 minutes, and the supernatant was taken to measure the absorbance at 541 nm using a UV-1750 ultraviolet-visible spectrophotometer. Each group was operated in parallel 3 times, and the hemolysis rate was calculated according to formula (3).

[0081]

[0082] Biosorption study: 200±20g healthy SD rats were taken and kept for at least one week before the experiment to fully adapt to the environment. After fasting and free drinking water for 8h, they were killed, and the small intestine was removed and the contents were rinsed with saline. The small intestinal mucosa should be kept intact and cut into 2cm×3cm flattened fragments and placed on a glass slide for use. The precisely weighed N-MSN, CMR-L-MSN, CMR-D-MSN (all 20mg); IMC (5mg); IMC loaded into N-MSN, IMC loaded into CMR-L-MSN, IMC loaded into CMR-L-MSN (all containing 5mg IMC) samples were evenly spread on the prepared small intestinal tissue samples and moistened with a small amount of saline. Then, the slide was tilted to a 45° angle with the horizontal plane and rinsed with 37℃ pH 6.8 PBS buffer at a flow rate of 2ml / min, and the rinsing fluid was collected every minute for a total of 5min. The rinse solution containing the carrier was first centrifuged, washed, and dried before being weighed to quantify the bioadhesion capacity of the carrier. The rinse solution of the drug and the drug-loaded carrier was ultrasonically extracted to completely extract the drug in the pores. The absorbance of the eluted drug was measured at a wavelength of 318 nm using a UV-1750 ultraviolet-visible spectrophotometer and converted into weight to calculate the adhesion rate. All samples were operated in parallel 3 times, and the bioadhesion rate of the samples was calculated according to formula (4).

[0083]

[0084] Conclusion: Hemolysis test and bioadhesion test were used to evaluate the biological properties of CMR-L-MSN and CMR-D-MSN. The hemolysis results showed (Fig.7A and 7B) that the hemolysis rates of N-MSN, CMR-D-MSN and CMR-L-MSN were positively correlated with the concentration. The hemolysis rate of N-MSN was concentration-dependent and increased significantly with the increase of concentration. When the concentration reached 400μg / ml, the hemolysis rate exceeded 10%. The hemolysis rate of MSNs-COOH only increased slightly with the increase of concentration, but it was less than 5% in the concentration range of 100μg / ml to 800μg / ml. The hemolysis rate was extremely low, with good blood compatibility, which met the requirements for biomaterials. As an orally absorbed drug IMC, the intestine is its main absorption site, and the adhesion of the drug to the intestinal epithelial tissue is the prerequisite for its absorption. Therefore, this study further investigated the bioadsorption of silica carriers and their drug delivery systems in the intestinal mucosa. The intestinal adsorption curves are shown in Fig. 7C and 7D. With the increase of dissolution medium rinsing time, the bioadsorption rates of N-MSN, CMR-D-MSN, CMR-L-MSN; IMC, IMC loaded into N-MSN, IMC loaded into CMR-D-MSN and IMC loaded into CMR-L-MSN gradually decreased. After slowly rinsing with pH 6.8 PBS solution for 5 minutes, the bioadhesion rates of CMR-D-MSN (90.3±1.1%) and CMR-L-MSN (89.7±1.3%) were significantly higher than those of N-MSN (82.5±1.0%) (p<0.01). The bioadhesion rate of the model drug IMC is 71.7±0.5%. When IMC is loaded into CMR-D-MSN (86.4±0.3%) and CMR-L-MSN (86.1±0.5%), its bioadhesion rate can be significantly increased (p<0.01), which is also significantly higher than the bioadhesion rate after IMC is loaded into N-MSN (79.6±0.7%) (p<0.01). It can be seen that CMR-D-MSN and CMR-L-MSN have stronger bioadhesion ability than N-MSN, because the carboxyl groups in CMR-D-MSN and CMR-L-MSN have strong affinity with the hydrophilic proteins on the membrane and thus have good mucosal adhesion ability.

[0085] Example 6 In vivo biological effects

[0086] 1. In vivo pharmacokinetics

[0087] 1.1 Dosage regimen

[0088] Twelve male SD rats weighing 200±20g were randomly divided into 4 groups (IMC group, IMC loaded into N-MSN group, IMC loaded into CMR-L-MSN group and IMC loaded into CMR-L-MSN group), with 3 rats in each group. The rats were fed for one week before the experiment to fully adapt to the environment, fasted for 12h before administration, and had free access to water. The dosage of IMC and drug carrier was 35mg / kg (including IMC), and the samples were suspended in 2ml of normal saline and administered to rats by gavage (10ml / kg ig). At designated time points after administration (0.5h, 1h, 1.5h, 2h, 3h, 4h, 6h, 8h, 12h, 24h, 36h and 48h after administration of IMC and drug-loaded carrier), blood (about 0.5ml) was collected from the orbital vein of the rats and anticoagulated in a centrifuge tube pre-coated with sodium heparin (10% sodium heparin saline infiltrated, v / v), and plasma was collected by centrifugation at 10000rpm for 5min. The obtained plasma was then frozen in a -20℃ refrigerator for future use.

[0089] 1.2 Blood drug concentration determination

[0090] High performance liquid chromatography (HPLC) was used to analyze the blood concentration of IMC. The specific operation was as follows: 80 μl of internal standard solution (methanol solution with 400 μg / ml NMS as internal standard) was accurately added to 200 μl of plasma, 20 ml of methanol was added, and then 400 μl of acetonitrile was added, vortexed for 2 min, centrifuged at 10000 rpm for 5 min, and 20 μl of the supernatant was injected for HPLC analysis. The HPLC analysis conditions were Diamonsil C18 column (250×4.6 mm, 5 mm); mobile phase: methanol-pH 7.3KH2PO4 buffer (66 / 34, v / v); detection wavelength: IMC, 320 nm; flow rate: 1.0 ml / min; column temperature: 25°C.

[0091] 2 Anti-inflammatory pharmacodynamics

[0092] 2.1. Dosage regimen

[0093] The anti-inflammatory biological effect of the drug-loaded preparation was evaluated by the rat ankle swelling test. Fifteen male SD rats (200±20g) were randomly divided into five groups (normal saline group, IMC group, IMC loaded into N-MSN group, IMC loaded into CMR-L-MSN group and IMC loaded into CMR-L-MSN group), with three rats in each group. The rats were kept for one week before the experiment to fully adapt to the environment, and fasted overnight before administration but not water. Rats in the negative control group were replaced with normal saline to induce swelling only, rats in the positive control group were gavaged with the raw material containing IMC at a dose of 35mg / kg, and rats in the experimental group were gavaged with the drug-loaded carrier containing the same dose of IMC.

[0094] 2.2 Measuring foot swelling

[0095] The ankle circumference of the right hind foot of the rats was measured before administration. 30 minutes after administration, 0.1 ml of λ-carrageenan (1%, w / v, 10 mg / ml) was injected into the right hind ankle of each rat to induce unilateral foot swelling to construct an acute inflammation model. The ankle circumference of the right hind paw was measured at predetermined time intervals (0.5 h, 1 h, 1.5 h, 2 h, 3 h, 4 h, 5 h), and the swelling rate was calculated according to formula (5).

[0096]

[0097] Inflammatory factors

[0098] 4 h after the preparation of the inflammation model, blood (about 1 ml) was collected from the orbital vein of the rats, and then centrifuged at 3000 rpm for 10 min to obtain serum and stored at -80 ° C for analysis. Then, the expression levels of IL-1β and TNF-α inflammatory factors in serum were determined by ELISA kits according to the manufacturer's instructions, and the absorbance (OD value) was measured at 450 nm using a SpectraMAX Plus 384 microplate reader (Shanghai, China) to determine its concentration.

[0099] 2.4. Tissue section examination

[0100] After blood was drawn from the rats, the inflamed area of ​​the right hind paw was removed, and the tissue of the inflamed area was removed and fixed with 4% paraformaldehyde fixative, dehydrated, and embedded in conventional paraffin, and the sections (thickness 5 μm) were dewaxed and finally stained with hematoxylin-eosin (H&E). The sections of the rat inflamed tissue were observed under an optical microscope and examined. The sections were imaged (×100, ×400) using a BA200 Digital trinocular camera microscope system (Fujian, China). The severity of arthritis was evaluated based on pathological changes such as inflammatory cell infiltration, joint swelling, inflammation, and pannus formation.

[0101] 3 Statistical analysis

[0102] Data results are expressed as mean ± standard deviation (SD). One-way analysis of variance (ANOVA) and Tukey's multiple comparisons were used to determine the differences between independent groups. All data were analyzed using Prism Version 6.0 (GraphPad) software, and p values ​​< 0.05 were considered significant.

[0103] Conclusion: To further reveal the biological effects of CMR-L-MSN and CMR-D-MSN in vivo, pharmacokinetic and anti-inflammatory pharmacodynamic experiments were conducted in this study. The main pharmacokinetic parameters and blood concentration-time curves after oral administration are shown in Fig.8Aand Table 2. The blood concentration of IMC in 1-12h after being loaded into CMR-L-MSN (Cmax=91.2±9.3mg / l) and CMR-D-MSN (Cmax=107.0±9.8mg / l) also increased significantly, which was significantly higher than that loaded into N-MSN (Cmax=67.3±8.4mg / l). Among them, CMR-D-MSN had a higher blood concentration and a longer half-life. In addition, CMR-L-MSN and CMR-D-MSN have obvious advantages in improving drug bioavailability (IMC is loaded into CMR-L-MSN: 1709±103%; IMC is loaded into CMR-D-MSN 2338±125%), and their bioavailability is 2.0 and 2.7 times higher than that of IMC, respectively. The above results show that CMR-L-MSN and CMR-D-MSN have obvious advantages in improving drug bioavailability, which is consistent with the dissolution results. The main reasons are that the IMC in CMR-L-MSN and CMR-D-MSN are both amorphous, and their solubility is higher than that of crystalline IMC; secondly, the larger specific surface area and carboxyl groups of CMR-L-MSN and CMR-D-MSN make it easier for the drug carrier to adhere to the intestinal wall of the small intestine (consistent with the results of the bioadhesion experiment), increasing the chance of absorption. The drug-loading space provided by its internal pores also improves the stability of the drug in body fluids, thereby allowing the drug to have a higher blood concentration for a long time and to fully exert its long-term effect, which is consistent with the in vitro dissolution results.

[0104] The anti-inflammatory effect of IMC in CMR-L-MSN and CMR-D-MSN was further studied by establishing a rat foot swelling model. The results of foot swelling showed (Fig.8B) that the swelling rate of rats in the saline group gradually increased over time, indicating that the rat foot swelling model was successfully established. Compared with the saline group, the swelling rate of the IMC positive group decreased. When IMC was loaded into CMR-L-MSN and CMR-D-MSN, the swelling rate was significantly reduced (the λ-carrageenan solution took effect 1h after injection) (p<0.05), and was significantly lower than that of N-MSN after drug loading. The experimental results of inflammatory factors showed that the concentrations of TNF-α and IL-1β in the saline group were significantly higher than those in the blank control group (p<0.01), which further proved that the model was successfully established. After IMC treatment, the concentration of inflammatory factors was significantly reduced. When IMC was loaded into CMR-L-MSN and IMC was loaded into CMR-D-MSN for treatment, the concentrations of TNF-α and IL-1β in the blood were significantly reduced (p<0.01), and were significantly lower than those of IMC loaded into N-MSN (Fig.8C). Pathological examination of inflammatory tissue showed that the skin tissue structure of the normal control group was complete and clear, the cytoplasm was uniform, and the nucleus morphology was normal. In the saline group, more necrosis and dissolution were seen at the bottom of the dermis, surrounded by more lymphocytes and neutrophils infiltration. Compared with the normal group, the pathological changes were obvious. The pathological changes of the skin tissue in the IMC group were milder, and a small amount of necrosis and dissolution were seen at the bottom of the dermis and the subcutaneous muscle layer, surrounded by a small amount of lymphocytes and neutrophils infiltration. More noteworthy is that the skin tissue lesions of CMR-L-MSN and CMR-D-MSN loaded with IMC were significantly improved (low inflammatory cell infiltration) (Fig.8D). The above results all confirm that CMR-L-MSN and CMR-D-MSN have strong anti-inflammatory effects when delivering IMC due to the improved oral bioavailability, and CMR-D-MSN has a better anti-inflammatory effect. The above results show that CMR-L-MSN and CMR-D-MSN with molecular chiral functions, especially CMR-D-MSN with D configuration, have potential research value in the construction of delivery systems for achiral oral drugs.

[0105] In summary, CMR-L-MSN and CMR-D-MSN with chiral microenvironment stimulus response were successfully prepared by using new chiral silicon coupling agent TESPSA-L-Pro or TESPSA-D-Pro as auxiliary structure-directing agent for synergistic self-assembly. Characterization results show that CMR-L-MSN and CMR-D-MSN are spherical nanoparticles with rough surface, high specific surface area and hidden channels, and have opposite chiral characteristics. DSC and XRD analysis confirmed that most of the crystalline IMC loaded into CMR-L-MSN and CMR-D-MSN has been transformed into an amorphous state of amorphous phase. In vitro drug release studies have shown that after IMC is loaded into CMR-L-MSN and CMR-D-MSN, its solubility can be significantly improved compared with N-MSN in the corresponding dissolution medium (p<0.05), showing different chiral recognition drug release functions in the in vitro chiral environment. CMR-D-MSN has a better drug release effect, and wettability experiments have further confirmed this rule. Hemolysis experiments and intestinal adsorption experiments also confirmed that CMR-L-MSN and CMR-D-MSN have good blood biocompatibility and intestinal adsorption capacity. The anti-inflammatory pharmacodynamics and pharmacokinetic results showed that CMR-L-MSN and CMR-D-MSN have higher bioavailability for IMC than N-MSN, and can deliver more drugs in the body, thus showing a stronger anti-inflammatory pharmacodynamic effect. Among them, since CMR-L-MSN and CMR-D-MSN have different chiral recognition functions, CMR-D-MSN can increase the release of IMC after responding to the in vivo environment and show stronger anti-inflammatory pharmacodynamic performance. In summary, CMR-L-MSN and CMR-D-MSN (better) show good drug delivery performance for oral water-insoluble achiral drugs IMC both in vivo and in vitro, which has potential research value for constructing water-insoluble achiral anti-inflammatory drug delivery systems, and will also provide valuable guidance for the development and application of chiral materials in the medical field.

Claims

1. A method for preparing chiral mesoporous silica nanoparticles, characterized in that: The following steps are involved: (1) The chiral silicon coupling agent TESPSA-L-Pro or TESPSA-D-Pro is synthesized by the hydrolysis condensation reaction of L-proline or D-proline and 3-(triethoxysilyl)propyl succinic anhydride. The structural formula of TESPSA-L-Pro is: The structural formula of TESPSA-D-Pro is (2) Hexadecyltrimethylammonium bromide was used to associate to form micelles, and TESPSA-L-Pro or TESPSA-D-Pro was added to form a micelle template with siloxane groups. Then, tetraethyl orthosilicate was added to react with the siloxane part of the micelle template to form a silicon skeleton. The template was removed to obtain chiral mesoporous silica nanoparticles CMR-L-MSN and CMR-D-MSN.

2. The method for preparing chiral mesoporous silica nanoparticles according to claim 1, characterized in that: In step (1), the molar ratio of L-proline or D-proline to 3-(triethoxysilyl)propyl succinic anhydride is 1:2 to 2:1, preferably 1:

1.

3. The method for preparing chiral mesoporous silica nanoparticles according to claim 1 or 2, characterized in that: Step (1) is to ultrasonically disperse L-proline or D-proline in anhydrous acetonitrile to form a suspension, and then drip triethylamine and 3-(triethoxysilyl)propyl succinic anhydride dissolved in dry acetonitrile under stirring, and continue stirring until the reaction is completed, and then remove the solvent by rotary evaporation, and then dissolve the remaining crude product in ethyl acetate, and adjust the pH value to 4.5-5.5 and then repeat the extraction, and after the organic phase obtained by extraction is dried over sodium sulfate, it is dissolved in anhydrous ethanol and dichloromethane to evaporate the obtained white hygroscopic foam, which is the novel chiral silicon coupling agent TESPSA-L-Pro and TESPSA-D-Pro.

4. The method for preparing chiral mesoporous silica nanoparticles according to claim 3, characterized in that: The step (1) is carried out under ice bath conditions.

5. The method for preparing a novel chiral mesoporous silica nanoparticle according to claim 1, characterized in that: Step (2) is to place hexadecyltrimethylammonium bromide in a beaker, add deionized water and anhydrous ethanol, stir until dissolved, and add ammonia water and TESPSA-L-Pro or TESPSA-D-Pro in sequence under stirring, then drop ethyl orthosilicate and continue stirring, after standing for 24 hours, centrifuge for 5 to 10 minutes to obtain a white precipitate, wash it with deionized water and ethanol, and obtain novel chiral mesoporous silica nanoparticles CMR-L-MSN and CMR-D-MSN.

6. A method for preparing a novel chiral mesoporous silica nanoparticle according to claim 1 or 5, characterized in that: In step (2), the molar ratio of hexadecyltrimethylammonium bromide to the novel chiral silicon coupling agent TESPSA-L-Pro or TESPSA-D-Pro is 2:1 to 4:

1.

7. The method for preparing a novel chiral mesoporous silica nanoparticle according to claim 6, characterized in that: The molar ratio is preferably 3:

1.

8. The method for preparing a novel chiral mesoporous silica nanoparticle according to claim 5, characterized in that: The centrifugal speed is 10000-12000 rpm.

9. Chiral mesoporous silica nanoparticles prepared by the method of claims 1 to 8.

10. Use of chiral mesoporous silica nanoparticles prepared by the method of claims 1 to 8 as drug carriers.